A study on faeto-maternal outcome in pregnancy with jaundice due to hepatitis E - Jena, Sushanta Kumar; Mohanty, Minakshi; Behuria, Sasmita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hepatitis E virus is a non-envelope RNA virus responsible for large epidemics in Asia, the Middle east Mexico and Africa. It spreads via the feco-oral route, and has an incubation period of 8-10 weeks. The objective of the study was to find out the effect of hepatitis E during pregnancy on faeto-maternal outcome. Methods: A study on faeto-maternal outcome of 38 pregnant women admitted with jaundice due to hepatitis E to the Department of Hepatology, Shri Ramachandra Bhanj (SCB) Medical College, Cuttack, Odisha, India during January 2015 to December 2015. Results: 38 Pregnant women admitted to the Department of Hepatology of SCB Medical College, Cuttack, Odisha, India were studied. 65.7% were from rural area, 92.1% were in their third trimester of pregnancy. Serum bilirubin >10 mg in 52.19 %, SGOT, SGPT and alkaline phosphatase were raised in majority of them. Out of 38 women 32 delivered and 6 remain undelivered. In 81.25% of cases labor was spontaneous, perinatal mortality was observed in 46.87% of cases and 5 women died during child birth. Conclusions: When pregnancy is associated with jaundice due to hepatitis E, there is high perinatal and maternal morbidity and mortality. Early diagnosis and careful management is required for such cases.